Causes and consequences of the war in eastern Ukraine: An economic geography perspective - Mykhnenko, V (Taylor and Francis, 2020)
This essay provides an economic geography perspective on the causes and consequences of the war in eastern Ukraine. It focuses on the controversial proposition that the armed conflict in 2014 was triggered by domestic, economically determined factors. The essay argues that economic and material circumstances in the region had generated neither necessary nor sufficient conditions for a locally rooted, internally driven armed conflict. The role of the Kremlin’s military intervention was paramount for the commencement of hostilities. As the human and economic costs of the war continue to mount, Ukraine’s war-ravaged eastern regions face further depopulation, economic decline and erosion of development.